Influence of chlorhexidine dentin disinfection on universal adhesive performance: Interfacial adaptation and bond strength assessments. - Alaa Turkistani; Helal M Sonbul; Mai Almarzouki (PLoS ONE)
Purpose This study aimed to investigate the effect of chlorhexidine (CHX) cavity disinfectant on interfacial microleakage and micro-tensile bond strength (μTBS) of a universal adhesive bonded to dentin in both self-etch (SE) and etch-and-rinse (ER) modes. Methods Class I cavities were prepared in the coronal dentin of extracted human teeth and assigned to two etching modes (SE or ER), then subdivided by disinfection with or without CHX (n = 5). Cavities were restored using Single Bond Universal Adhesive and Filtek Z350 XT composite. After 10,000 thermal cycles, interfacial microleakage was assessed on serial B-scans obtained for each specimen using cross-polarization optical coherence tomography. For μTBS testing, resin composite was bonded to dentin discs, sectioned into beams, and subjected to tensile load until failure using a universal testing machine. Failure modes in fractured beams were analyzed under a stereomicroscope and categorized as adhesive, cohesive, or mixed. ANOVA with Bonferroni post-hoc at a significance level of 0.05 was used to compare the groups. Results Microleakage was not significantly influenced by the etching mode or CHX disinfection (p-value = 0.068). For μTBS, the ER group exhibited the highest values, and CHX disinfection did not significantly alter these results (p-value = 1.000). In contrast, the SE-CHX group displayed significantly lower μTBS than the ER, ER-CHX, and SE groups (p-values of <0.001, <0.001 and 0.012, respectively). ER mode primarily resulted in adhesive failures, regardless of CHX. SE group exhibited both adhesive and cohesive failures, while SE-CHX mostly showed adhesive failures. Conclusion The use of CHX disinfectant influences the bonding performance of universal adhesive differently depending on the application mode. Specifically, in the SE mode, CHX adversely affects bond strength to dentin. This suggests that when using universal adhesives in SE mode, clinicians should carefully consider the use of CHX disinfectants, as they may interfere with the adhesive's effectiveness.